Hipoparatiroid: Deteksi Awal dan Cara Penegakan Diagnosis: Hypoparathyroidism: Early Detection and Diagnosis Approaches - Rizqina Alya Shafa; Dewa Ayu Vania Novista Anjani; I Komang Gede Andhika Wibisana; Nasyada Fadhila Rahmadini; Pratiwi Anggraini; Raditya Bayu Farizil Akhyar; Reny Apriyani; Sicillia Putri Atari; Yoga Pamungkas Susani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Hypoparathyroidism is an endocrine disorder characterized by low or even absent production of parathyroid hormone (PTH). The most common cause of hypoparathyroidism is injury to the parathyroid gland or accidental removal during thyroid surgery. The diagnosis of hypoparathyroidism is made by assessing clinical symptoms, physical examination and laboratory tests. The author wants to know more about how to detect early and diagnose hypoparathyroidism. Hypoparathyroidism is an endocrine disorder characterized by low or absent production of parathyroid hormone (PTH). The most common cause of hypoparathyroidism is injury to the parathyroid glands or unintentional removal during thyroid surgery. The diagnosis of hypoparathyroidism is established through the assessment of clinical symptoms, physical examination, and laboratory tests. The author aims to explore further the early detection and diagnostic approaches for hypoparathyroidism.